Concreto autoadensável com cinza do bagaço da cana-de-açúcar - Molin Filho, Rafael Germano Dal (2012)
Self-compacting concrete (SCC) presents a fluid consistency as well as a cohesive self-compacting feature which enables it to fill molds and to pass through obstacles only through its own weight, without any segregation. Thus, self-compacting concrete casts off the use of mechanical stirrer at the initial step and at the compacting, reducing costs, time and steps for processes in building sites and prefabricated industries. Mineral additions and chemical additives are generally used for its composition. The material used was: calcitic limestone filer (mineral addition), GLENIUM 51 hyperplasticiser (3rd generation polycarboxylic), cement CP II E 32, quartzite sands, basalt gravel, water and the ash from sugar cane bagasse, which is a by-product generated through the reuse sugar cane burned bagasse energetic in boilers. It is estimated for 2012/2013 harvest the generation of 268.000 t of CBC, which was applied as fine aggregate partially replacing sand. Thus, the aim was the contribution to a decreasing in sand extraction and to a development of a technical destination with aggregate value for the bagasse. The self-compacting parameters were classified by ABNT NBR 15823-1:2010 e criteria, by Gomes and Barros (2009). The self-compacting tests applied were: Slump Flow Test to evaluate plastic fluidity, draining and viscosity; V-Funnel Test to evaluate viscosity, L-Box Test, J-Ring Test to evaluate bandwidth ability and, U-Pipe Test to evaluate resistance to segregation. The single feature, in mass, which was developed from SCC with CBC was 1: 1,8: 0,2: 2,21: 0,45: 0,40: 0,0055 (cement: sand: CBC: gravel: water: filer: hyperplasticiser). The development of of SCC without CBC presented a single feature, in mass, similar to 1: 2: 2,12: 0,45: 0,40: 0,0055 (cement: sand: gravel: water: filer: hyperplasticiser), being different only in 0,009 for gravel relation and for CBC partial presence when replacing sand). Both features had their aspects evaluated by at least one of the criteria followed, where SCC with 10% CBC, replacing sand, reached all parameters recommended by ABNT NBR 15823-1:2010. The SCC with 10% CBC partially replacing sand has met all standards set by ABNT NBR 15823-1:2010. Compressive strength and tensile strength performances for the 28 days were both satisfactory. It was possible to classify them as belonging to a resistance class I and C35 group through ABNT NBR 8953:1992. Cement consumption was 401 kg/m3 for SCC without CBC and 396 kg/m3 for CAA with CBC, a difference of 1.2%, establishing, thus, that CBC did not provide a meaningful change in cement consumption. However, CBC replacing sand at 10% rate provided a decreasing of 89.2 kg/m3 in sand consumption. It was observed, though, that replacing 10% of sand for CBC in the developed SCC feature does not change the rheological characteristics and keeps the same fluidity, cohesion and consistency aspects, as well as it does not produce any changes in mechanical properties. It can therefore be established that it is possible to use CBC in SCC production without having its rheological characteristics and mechanical properties damaged reducing thus sand consumption.